Signal irrelevance of corporate governance practices during Initial Public Offerings in India - Handa, Rekha; Singh, Balwinder; Sharma, Sharad (The journal of contemporary issues in business and government, 2019)
A sample of initial public offerings (IPOs) of firms listed on the Bombay Stock Exchange between April 2003 and March 2014 has been used to investigate the relevance of corporate governance in the post-IPO capital market performance. Signal theory has been used to understand the phenomenon of post-IPO capital market performance vis-à-vis signal cast by corporate governance attributes. The study finds investors ’ indifference to governance mechanis m put in place by IPO-firms in compliance with the listing requirements. The outcomes of the study provide essential feedback for IPO-firms and the Security Exchange Board of India, the Indian capital market regulator.